The wayfinder : a novel [large type] - Johnson, Adam, 1967- (Thorndike Press large print top shelf., 2025)
"Talking corpses, poetic parrots, and a fan that wafts the breath of life--this is the world young Kōrero finds herself thrust into when a mysterious visitor lands on her island, a place so remote its inhabitants have forgotten the word for stranger. Her people are desperate and on the brink of starvation, and the wayward stranger offers them an impossible choice: they can remain in the only home they've ever known and await the uncertainty to come, or Kōrero can join him and venture into unfamiliar waters, guided by only the night sky and his assurance of a bountiful future in the Kingdom of Tonga. What Kōrero and her people don't know is that the promised refuge is no utopia--instead, Tonga is an empire at war and on the verge of collapse, a place where brains are regularly liberated from skulls and souls get trapped in coconuts with some frequency. The perils of Tonga are compounded by a royal feud: loyalties are shifting, graves are being opened, and everyone lives in fear of a jellyfish tattoo. Here, survival can rest on a perfectly performed dance or the acceptance of a cup of kava. Together, the stranger and Kōrero embark upon an epic voyage--one that will deliver them either to salvation or to the depths of the Pacific"--